The Role of Assimilate Dynamic in Rice Grain Filling Under Two Nitrogen Conditions - Nurhermawati, Renica; Lubis, Iskandar; Junaedi, Ahmad (Trends in Sciences, 2023)
The assimilate obtained during the grain filling phase is sourced from photosynthesis and Non Structural Carbohydrate (NSC) reserves produced during the vegetative phase in the vegetative organs. Assimilate from different sources plays different roles in the grain filling process. This study aims to investigate varietal difference on assimilate distribution, nitrogen response and yield performance. The experiment was carried out in the rice fields of Petapahan Village, Kampar Regency, Riau. The experimental design used was a split-plot in randomized complete block design (RCBD) with 2 factors and 3 groups. The first factor, as the main plot, was the condition of N. Specifically without N (NoN) (0 kg ha−1 urea) and treatment with normal N (NN) (250 kg ha−1 urea). The second factor, as a sub-plot, was rice variety, spesifically Hipa 18, IPB 3S, Ciherang, and Way Apo Buru. Hipa 18 was a variety having the largest reserves of NSC. A positive correlation was found between plant characters observed in this research, they are stem and leaf dry weight, total carbohydrates in stems (proximate analysis), photosynthetic rate, and leaf nitrogen content (Kjeldahl method). As well as other agonomic characters such as leaf area index and yield components. The highest dry weight of stems and leaves of Hipa 18 was at the heading phase, 22.6 g. While the highest carbohydrate content of the stems of the variety was 7.93 g in the same phase. This large NSC reserve supported the largest sinks as well at Hipa 18. However, the source capacity of the varieties used was found to be lower than the sink capacity. It was also known that nitrogen affected the condition of all plant characters observed in this study. Therefore optimal nitrogen fertilization is needed to get a maximum yield. HIGHLIGHTS Production of dry matter through photosynthesis and remobilization of assimilate from vegetative organs are the main sources of grain filling There was a greater amount of assimilate remobilization in Hipa 18 compared to IPB 3S, Ciherang, and Way Apo Buru The yield was positively correlated with plant height at harvest, stem and leaf dry weight, leaf N content, leaf area index, total stem carbohydrates, and photosynthesis GRAPHICAL ABSTRACT